Three-dimensional stability assessment of slopes in intact rock governed by the Hoek-Brown failure criterion - Park, Dowon; Michalowski, Radoslaw L. (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2021)
Three-dimensional failure analyses of slopes are rather elaborate, and for rock slopes, where the rock strength is defined by nonlinear failure envelopes, they are particularly intricate. This is why many earlier approaches used a linear approximation of the strength envelope prior to carrying out the stability analysis. This approximation is avoided in this paper, thanks to using the parametric form of the Hoek-Brown failure criterion. The kinematic approach of limit analysis is used as the method of study. An argument is brought forward that even though rocks tend to fracture at low confining stresses, the ductility of deformation prior to a brittle drop in stress during failure may be sufficient for limit analysis theorems to be applicable. Two measures of rock slope stability are evaluated: the stability number and the factor of safety. Numerical results are presented in the form of charts and tables. Because the limit analysis used allows one to evaluate the rigorous bounds on true solutions, it was possible to demonstrate that the method employed in the paper yields more accurate results than the approaches used formerly in the subject literature. A new and efficient mechanism of failure was devised for very narrow rock slopes.